Redactie Het Volk. V.l.n.r.: De Roode, Ankersmit, Tak, Polak, Vliegen. Op tafel het nummer van Zondagsblad van 22 april 1906 - Leenheer, Corn.
Redactie Het Volk. V.l.n.r.: De Roode, Ankersmit, Tak, Polak, Vliegen. Op tafel het nummer van Zondagsblad van 22 april 1906.